Effectiveness of Group and Individual Cognitive-Behavior-Therapy on Depression and Depression Reduction Effects on Marital Satisfaction and Sexual Relationships Among Menopausal Iranian Women - Khoshbooii, Robab (2011)
Transition to menopause is marked by significant physiological and emotional changes that are distressing for a number of women and may lead to depression. Cognitive Behavior Therapy (CBT) as an effective intervention has been examined on different disorders and population and, but in the case of Iran, although CBT has also been practiced, it has not been done on menopausal women. Therefore, the main purpose of this study is to examine the effectiveness of CBT on depression among Iranian women around menopause and explore the impact of reduction of depression on marital satisfaction and sexual relationship among this group of Iranian women. This study was conducted as an experimental design with pre-test, post-test and four weeks follow-up. Seventy-two women aged 40-55 years who met DSM-IV criteria for major depression were recruited through multi-stage random sampling from four health centers in the municipality of Tehran, Iran and randomly assigned to two experimental groups and one control group. The experimental groups underwent group cognitive behavior therapy (G-CBT) or individual cognitive behavior therapy (I-CBT) for depression while the control group received regular treatment on menopause. Instruments for data collection included Beck Depression Inventory (BDI-II), ENRICH-marital satisfaction, and ENRICH-sexual relationship questionnaires, which were completed by the participants three times. Results of repeated measure ANOVA for G-CBT and I-CBT illustrated that there was a statistically significant difference in the depression scores over time for both experimental groups p<.05 , partial effect size p2 =.92 and p2 =.95 respectively. Furthermore, running MANOVA test revealed that there was a significant difference in marital satisfaction and sexual relationship in follow-up measurements between three groups p<.05, partial effect size p2 = 0.60, p2 =.65 respectively, indicating that the mean differences between groups are large. These results demonstrated that the treatment, comprised of 16 sessions of group CBT or eight sessions of individual CBT intervention for major depression, appears feasible and produced favorable treatment outcomes among Iranian women with major depression around menopause period. Second and third outcomes indicate that the treatment of depression is effective in improving marital satisfaction and sexual relationship and leads to significant changes in these factors among participants of the experimental groups. The findings of the present study, firstly, support the effectiveness of the cognitive behavioral therapy (CBT) approach in terms of reducing depression among Iranian women around menopause period. Secondly, indicate that depression, marital satisfaction and sexual relationship tend to change simultaneously in women around menopause period. The findings of this study have implications for menopausal and mental health clinics, marriage and family therapy centers and physicians who provide treatment for women around menopause period. In general, the findings also may have implications on counseling psychology theory and specifically on CBT. Group therapy appears to be a more beneficial and cost-effective alternative to individual therapy especially for CBT. Future studies may be needed to replicate the findings and for generalization.